SYSTOLIC BLOOD PRESSURE REDUCTION: DO ALL THE DRUGS HAVE THE SAME EFFICIENCY? - S. V. Nedogoda (Рациональная фармакотерапия в кардиологии, 2015)
The article provides the large prospective researches data which testify the more important role of systolic blood pressure increase in arterial hypertension forecast. Here comes the conclusion that the most perspective drugs for systolic blood pressure reduction today are diuretics. Indapamid SR (Arifon retard) stands out for its efficiency and safety among diuretics.